Abadi: safeguarding the rich fabrics of Malay architectural heritage through a ceremonial entrance of IIUM Malay Enclave - Wafa, Leslous; Abdullah, Fadzidah; Alias, Ulfah Awatif Umairah; Abg Azahari, Abang Nurazizan; Azmin, Aida Kesuma; Hasan, Sharina Farihah (IIUM Press, 2025)
This article presents a project on “ceremonial entrance” for the existing Malay Enclave, also called the Malay Heritage Living Lab, at International Islamic University Malaysia. The proposed project incorporates a lookout platform, an entrance archway, bridge guardrails, and landscape works. The main objective of this inventive design proposal is to elevate the Malay Heritage Living Lab, infusing it with captivating elements that are not only safeguarding the rich fabric of traditional Malay architectural heritage but also function as a guiding light to both local and international audiences. In essence, the design concept Abadi, stands as a testament to the legacy of bygone eras, offering an immersive experience that effortlessly intertwines the delicate strands of traditional Malay architecture and the quintessential elements inherent to a traditional village setting. To accomplish this vision, an elaborate and systematic approach was carefully developed. This entailed the selection of case studies, each dedicated to exploring a unique aspect of the proposed design: the structure, the passageway, and, importantly, the platform. Throughout this process, the research team explored extensively into the venture of identifying characteristics that delineate each design element. This encompassed a thorough examination of materials, installation techniques, and a thoughtful choice of hues, all of which were scrutinised with great attention to detail, tailored precisely to the context and specific needs of the project. As the project takes shape, it would be supported by a set of core conceptions that encapsulate its essence and goals, with Rumah Kutai (Kutai House) being particularly prominent context to the proposed project. The notion of Abadi, means eternal, everlasting, or immortal, would serve as guiding principles, ensuring that the design remains rooted in the Malay cultural origins and continues to respect and celebrate the vibrant heritage it strives to preserve and promote. Ultimately, this interdisciplinary undertaking promises to be an extraordinary blend of knowledge, creativity, and appreciation for Malay heritage in the contemporary context